Oxidative stability of soybean oil with antioxidant addition of Isaño (Tropaeolum tuberosum Ruiz & Pavón) during potato frying - Calsin Cutimbo, Marienela (2016)
The objective was to evaluate the oxidative stability of soybean oil with the addition of antioxidant of isaño (Tropaeolum tuberosum Ruiz & Pavón) and TBHQ during potato frying, analyzed at 0, 1,5, 2,5 and 3,5 hours At 180 ° C + 10 ° C, with frying intervals of potatoes every 30 minutes, performing eight frying events. To evaluate, peroxide, acidity, dienes and trienes were tested for indices. During the frying, soybean oil samples with the addition of extract Isaño showed less formation of dimer and triers compared to the sample of  soybean oil with TBHQ, indicating greater protective effect on the oxidative stability of soybean oil during frying, without However, this sample showed a higher correlation compared to the oil samples with the addition of Isano extract, due to the presence of residues of sugars in said extracts. The peroxide index and free fatty acid percentage indicators did not prove to be very reliable parameters for determining the oxidation stability of the frying oil.